2020
DOI: 10.1097/sap.0000000000002338
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topical Tacrolimus on Pedicled Flap Survival

Abstract: Purpose Skin necrosis is a known postoperative complication of mastectomies. The pathophysiology of tissue necrosis involves lymphatic congestion, followed by venous congestion and ultimately arterial insufficiency. Recent mouse model studies have shown topical tacrolimus to increase growth of lymphatic collateral vessels and decrease lymphedema, potentially obviating the cycle of necrosis and increasing skin survival. The purpose of this study was to investigate the effect of topical tacrolimus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…An abridged version of the techniques used in our animal model is described hereinafter; further detail may be gleaned from our original article 6 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An abridged version of the techniques used in our animal model is described hereinafter; further detail may be gleaned from our original article 6 …”
Section: Methodsmentioning
confidence: 99%
“…Our previous rodent study demonstrated significantly decreased full-thickness necrosis in pedicled dorsal skin flaps with topical tacrolimus as compared with petroleum jelly, with an average of 33.8% less necrotic area. 6 The purpose of this study was to investigate the vascular and histological differences between these 2 groups to identify the etiology of our previous research findings.…”
mentioning
confidence: 98%
“…To our knowledge, our study is the first to evaluate the prophylactic use of topical tacrolimus to decrease ischemia and skin necrosis after injury in the rat model. Our group has previously shown tacrolimus application after injury significantly decreased the total necrotic area compared with controls 3 . Upon further histological analysis, we also demonstrated topical tacrolimus increased arterial, venous, and lymphatic growth in areas that were most susceptible for ischemic damage 6 …”
Section: Discussionmentioning
confidence: 51%
“…Our group has previously shown tacrolimus application after injury significantly decreased the total necrotic area compared with controls. 3 Upon further histological analysis, we also demonstrated topical tacrolimus increased arterial, venous, and lymphatic growth in areas that were most susceptible for ischemic damage. 6 Although the regulation of angiogenic and lymphangiogenic factors involved with wound healing is complex, the pharmacokinetic effects of topical tacrolimus doses most likely are associated with lymphangiogenic mechanisms involved with T-cell inflammatory responses.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation